Prisões cautelares no processo penal - Santos, José Carlos Daumas (2009)
The present work approaches the legal requirements for the decree or maintenance of any action for a provisional arrest, as well as the pertinent constitutional principles. Chapter 1 discourses on the constitutional principles applicable to the provisional arrests, which are studied in chapter 2. Chapter 3 considers the arrest of the caught in flagrante delicto. Temporary arrests are discussed in chapter 4 and arrests through pronunciation and appealable punishment sentence, in chapter 5. The preventive custody is examined in chapter 6 and chapter 7 focuses on the relative subject to the free on parole. Chapter 8 discourses upon the provisional arrest within the criminal and special prosecution criminal laws, and chapter 9 acknowledges the project for the reform os the criminal prosecution code, in what it regards to the writs of prevention. In chapter 10 the conclusions on the studied subject are composed